CREDIT CONTROL ON DEVELOPMENT - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Credit risk management is defined as identification, measurement, monitoring and control of risk arising from the possibility of default in loan repayments (Abdifatah& Ogle, 2010). Also Ogilo, (2012) defines Credit Risk Management to involve the process of making decisions relating to the investment of funds. Such decisions should be carefully analyzed as they are characterized by an element of uncertainty (Wanjira, 2010). Credit extended to borrowers may be at the risk of default such that whereas banks extend credit on the understanding that borrowers will repay their loans, some borrowers usually defaults and as a result, banks income decrease due to the need to provision for the loans (Gaitho, Wangui, 2010). Where the commercial banks do not have an indication of what proportion of their borrowers will default, earnings will vary thus exposing the banks to an additional risk ofvariability of their profits (Boateng, 2012). Every financial institution bears a degree of risk when the institution lends to business and consumers and hence experiences some loan losses when certain borrowers fail to repay their loans as agreed (Kairu, 2009).